Investigation and modeling of transport noise dependence on traffic speed and impact on population annoyance - Vilniškis, Tomas; Naimušin, Andrej; Januševičius, Tomas (Journal of Environmental Engineering and Landscape Management, 2022)
Transport noise is a serious problem in cities and has a negative impact on both health and economics. In addition to the aforementioned unnoticed health effects, traffic noise has also been identified as one of the leading causes of sleep disorders, annoyance and negative cardiovascular effects. This research consists of three parts: part one involves onsite measurements of traffic noise in Trakai town; part two simulates traffic noise at different average vehicle speeds; part three assesses the number of people affected by traffic noise. The carried-out simulation has demonstrated that the noise level changes very slightly at different average vehicle speeds. It should be noticed that more noise is generated at average vehicle speed of 30 km/h rather than at 50 km/h. The assessment of the annoyance level has disclosed that an average vehicle speed of 30 km/h should cause the highest level of annoyance (highest – 26.8%).